Mitochondrial Quality Control: A Pathophysiological Mechanism and Therapeutic Target for Stroke - Yang, Miaoxian; He, Yu; Deng, Shuixiang; Xiao, Lei; Tian, Mi; Xin, Yuewen; Lu, Chaocheng; Zhao, Feng; Gong, Ye (Frontiers in Molecular Neuroscience, 2022)
Stroke is a devastating disease with high mortality and disability. Previous studies have determined that mitochondria, as major regulators, are both modulated by stroke and further regulated development of post-stroke injury. Mitochondria involve in several biological processes such as energy generation, calcium homeostasis, immune response, apoptosis regulation, and reactive oxygen species generation. Meanwhile, mitochondria evolve various quality control systems including mitochondrial dynamics (fission and fusion), mitophagy to maintain the homeostasis of mitochondria network. The varied activity of mitochondrial fission and fusion are associated with mitochondrial integrity and neurological injury after stroke. Additionally, proper mitophagy seems to be neuroprotective for its effect of eliminating damaged mitochondria, while excessive mitophagy damages energy generation and mitochondrial-associated signal pathway. The balance of mitochondrial dynamics and mitophagy is more crucial than the absolute level of each process. Neurovascular unit (NVU) is a multidimensional system where cells release multiple mediators and regulate diverse signaling pathways across the whole neurovascular network in a way with highly dynamic interaction. Turbulences of mitochondrial quality control could lead to neurovascular unit dysfunction, including neuron death, neuroglia activation, blood brain barrier disruption, and neuroinflammation. However, the exact changes and effect of mitochondrial quality control in neurovascular unit after stroke have yet to be fully illustrated. In this review, we will discuss the updated mechanisms of mitochondrial quality control and the pathophysiology of mitochondrial dynamics and mitophagy after stroke. We highlight the regulation of mitochondrial quality control as a potential therapeutic target for both ischemic and hemorrhagic stroke.